Mineralogy, chemistry and stability of silt-size aggregates of soils from the Southeast Region of Brazil - Vitorino, Antonio Carlos Tadeu; Ferreira, Mozart Martins; Curi, Nilton; Lima, José Maria de; Silva, Marx Leandro Naves; Motta, Paulo Emílio Ferreira da (Pesquisa Agropecuaria Brasileira, 2003)
The objective of this work was to evaluate the relationship of soil mineralogical and chemical composition with stability of silt-size aggregates. The studies were carried out using samples of A and B horizons of some soils from the Southeast Region of Brazil. Fine-earth samples were dispersed at 12,000 rpm during 20 minutes and the silt fraction was separated through clay fraction drain, constituting the fraction named pseudo-silt, which was sonificated, separating the desegregated clay fraction (by sonication) from the properly named silt fraction. Correlation analyses showed that the soil mineralogical and chemical compositions have marked influence upon clay dispersion, with reflections on the silt fraction. Higher amounts of gibbsite reflect in higher stability of silt-size aggregates, while the kaolinite promotes inverse effect. The Al forms determined on the pseudo-silt fraction are associated with higher difficult of dispersion of clay fraction of soils.